Sustainability Practices and Financial Performance in SMEs: A Systematic Literature Review - Gde Agung Satria (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
In the post-COVID-19 pandemic era, businesses, particularly Micro, Small, and Medium Enterprises (MSMEs), have recognized that business activities should not only focus on economic profitability but also on environmental and social sustainability. However, the greatest challenge for MSMEs in implementing sustainable practices is closely related to cost efficiency and limited financial resources. Therefore, it is crucial for MSMEs to adopt sustainability practices that are aligned with their financial management strategies. Using a Systematic Literature Review (SLR) approach, this study aims to map the theoretical foundations underlying sustainability practices among MSMEs, examine their impact on financial performance, and identify the financial factors that drive their implementation. Based on an analysis of 27 articles published between 2013 and 2023, the findings reveal that four major theories dominate the literature in explaining sustainability practices among MSMEs. Furthermore, both internal factors (such as liquidity and cost efficiency) and external factors (such as access to green financing) are identified as the primary drivers of sustainability adoption. Theoretically, this study contributes to a broader understanding of the evolution of sustainable financial management in MSMEs from the pre-pandemic to the post-pandemic period. Practically, the findings provide valuable guidance for MSME practitioners in developing long-term sustainability strategies while maintaining financial stability.